Progressive Two-Stage Efficient Codigestion of Food Waste and Petrochemical Wastewater for Higher Methane and Hydrogen Production - Siddique, Md. Nurul Islam; Zaied, B. K.; M. Nomani, Kabir; M. F., Ahmad (Asian J. Chem, 2019)
The valorization of agro-modern waste through anaerobic codigestion signifies a remarkable prospect for waste treatment and sustainable energy source generation. This study intended to improve the codigestion of food waste and petrochemical wastewater by an advanced two-phase process. In view of concentric acidogenic and methanogenic stages, intended for upgrading execution and diminishing pollution. The ideal food waste to petrochemical wastewater proportion was assessed under batch operations. From that point, codigestion was carried out by continuous feeding operations weighting single-and two-phase digestions. The outcomes exhibited that the supplementation of petrochemical wastewater in codigestion with food waste incredibly improved the anaerobic system. The maximum methane generation was acquired codigesting the two wastes at equivalent proportion by utilizing the creative two-phase system. The proposed framework achieved the highest methane production of 259 mL/g volatile solid, which is more than double than the single-phase system and 11 % greater than that of conventional two-phase system.